Desenvolvimento de sensor baseado em eletrodo modificado com nanotubos de carbono contendo pentacianonitrosilferratos de metais para determinação de antioxidantes em microemulsão de biodiesel - Durigan, Bruna [UNESP] (2014)
In Brazil and in the world to search for alternative fuels has become increasingly important and biodiesel is considered a totally viable fuel compared to fossil fuels, due to their low emission of gases causing the greenhouse effect. However, its low oxidation stability is directly reflected in their quality, so synthetic antioxidants are the main compounds that have been used in the preservation of biodiesel against such oxidative processes. The determination of these compounds usually employs sophisticated techniques that require high costs. A viable alternative for their determination is the use of electroanalytical techniques for achieving low detection limits and lower cost, the use of chemically modified electrodes have great potential to expand the application range of the voltammetric technique, by providing greater selectivity and sensitivity. This paper presents the determination of the antioxidant BHT and TBHQ microemulsion biodiesel using a modified carbon nanotubes glass carbon electrode containing pentacianonitrosilferrado nickel and copper. According to the results , it was observed that the antioxidant TBHQ undergoes an oxidation potential in 53 mV vs (Ag/AgCl) in the middle of electrolyte compared with the potential obtained at a glassy carbon electrode is caused notable gain the modification due to a reduction potential of 130 mV and a gain value of three times of current. The microemulsion used was the biodiesel composition (composition 6% biodiesel with 21% NaCl electrolyte containing 0.5 mol L-1 in phosphate buffer 0.05 mol L-1 pH 7.0 and 73 % propanol ) . The study of concentration of TBHQ, using adsorptive stripping voltammetry technique module cyclical scan showed linearity in the concentration range of TBHQ 5.0x10-7 to 3.7x10-5 mol L-1 with a LOD of 4.1x10-7 in electrolyte support and 1.1x10-4 to 9.8x10-3 mol L-1 with a LOD of 8.4x10-5 mol L- 1 in microemulsion biodiesel, using the electrode NiPCNF-MWCNTs/GCE ...